2019
DOI: 10.1186/s12891-019-2456-9
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral kinematic characteristics in anterior cruciate ligament deficiency and reconstruction

Abstract: Background It is very important to dynamically evaluate the functional outcome in the knee after anterior cruciate ligament (ACL) reconstruction under physiological weight bearing. The objective of the current study is that we would like to compare the patellofemoral joint kinematics in three ACL status: ACL intact, ACL deficiency, ACL reconstruction. Methods Twenty patients with unilateral ACL deficient knees were recruited as preoperative group. Six months after ACL r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…For instance, fiducial points were used in this study for MRI-CT registration, since they are standard, simple, and applied in many clinical procedures, in particular when aligning bony landmarks. However, many other techniques have been proposed, like mutual information and iterative-closest-point techniques [31,33]. The use of fiducial points for MRI-CT registration showed a good accuracy in a previous investigation [31], with a mean distance between corresponding surfaces lower than 2 mm, consistent with the accuracy of the medical imaging techniques used in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For instance, fiducial points were used in this study for MRI-CT registration, since they are standard, simple, and applied in many clinical procedures, in particular when aligning bony landmarks. However, many other techniques have been proposed, like mutual information and iterative-closest-point techniques [31,33]. The use of fiducial points for MRI-CT registration showed a good accuracy in a previous investigation [31], with a mean distance between corresponding surfaces lower than 2 mm, consistent with the accuracy of the medical imaging techniques used in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Previous validation works showed an accuracy in knee kinematic reconstruction within 0.5 mm and 1 deg in the sagittal plane [30,32]. In this way, the experimental natural motion of the TF (i.e., the tibia-femur motion) and PF (i.e., the patella-femur motion) joints were obtained [33]. Registration was performed for both the flexion and extension movements, obtaining two motion curves: the volunteer unloaded motion was determined as the mean between the two.…”
Section: Image Data Post-processingmentioning
confidence: 95%
“…Several studies have reported excessive patellar lateral displacement and lateral tilt at 6 months after ACLR in either static or dynamic tasks. 16,17,33 One study reported increased patellar lateral rotation (valgus rotation) during a static lunge, 33 whereas others reported decreased patellar lateral rotation. 16,17 From a biomechanical standpoint, altered patellar kinematics may lead to decreased PFJ contact area and elevated contact forces, 28 suggesting detrimental effects on the articular cartilage of the patella and trochlea.…”
mentioning
confidence: 99%
“…Several studies have reported excessive patellar lateral displacement and lateral tilt at 6 months after ACLR in either static or dynamic tasks. 16,17,33 One study reported increased patellar lateral…”
mentioning
confidence: 99%
See 1 more Smart Citation